MODEL OF CALCULATIONS FOR EXPERIMENTALLY-OBTAINED GAS AND WATERPROOF SER-VICE LINE OPERATIONAL PARAMETERS - О. I. Stepanov; Е. E. Zaitseva; S. A. Khudyakova (Вестник Дагестанского государственного технического университета: Технические науки, 2020)
Abstract. Aim. Modelling and calculations were were carried out to justify the tactical capabilities of gas and smoke protection units of the fire and rescue units as primary units carrying out fire reconnaissance and rescue of victim s of fires. A methodology for assessing actions of personnel of fire departments when rescuing victims was analysed.Method. An experimental justification is given for the need to adjust the calculation methods for determining the working parameters of gas and smoke protection units when organising mass rescue of victims of a fire. A model is proposed for considering the actions of the fireteam of a gas and smoke protection service based on graph theory. Various approaches to forecasting operational parameters of gas and smoke protection units in fire services are considered.Results. Factors determining the limiting parameters of the gas and smoke protection units are presented along with examples for calculating operational parameters during mass rescue of victims of a fire.Conclusion. A conclusion is formulated regarding complicating factors of the work of the personnel of the gas and smoke protection service in the coefficient, considering the necessary air supply for the return trip, unforeseen circumstances and average air flow.